Manajemen Emosi dalam Perspektif Tafsir Al-Azhar: Studi Kisah Nabi Yunus dalam Al-Qur'an - Lathifah, Anisah Dwi; Yeti Dahliana (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study examines the concept of emotion regulation in the story of Prophet Yunus based on Hamka’s interpretation in Tafsir Al Azhar, using a psychological approach. The research background highlights the urgency of emotion regulation as a crucial skill in facing life’s challenges, particularly in the modern era, which is prone to stress, anxiety, and mental disorders. The novelty of this study lies in the thematic analysis of Qur’anic verses related to Prophet Yunus (Surah Ash-Shaffāt/37: 139–148, Surah Al-Anbiyā’/21: 87–88, Surah Al-Qalam/68: 48–50), integrating emotion regulation theories by James Gross, Oliver P. John, and Ross A. Thompson, along with Zakiah Daradjat’s Islamic psychology perspective. The research adopts a qualitative method based on library research with a descriptive-interpretative analysis. The findings reveal that Prophet Yunus regulated his emotions through stages of self-admission of faults, surrender to Allah, cognitive reappraisal, attentional deployment, and spiritual recovery, culminating in successful da’wah. The main factors influencing the effectiveness of his emotion regulation were steadfast faith and cognitive ability to reinterpret situations positively. The study concludes that effective emotion regulation requires a synergy between spirituality and psychological strategies.